Factors and challenges of driving reduction and cessation: A systematic review and meta-synthesis of qualitative studies on self-regulation. (June 2019) - Ang, Boon Hong; Jennifer, Oxley; Chen, Won Sun; Lee, Shaun Wen Huey
Abstract: Introduction : Older adults are at a greater risk of injury and death in a motor-vehicle accident. While the ability to drive safely can be challenging with aging, the concept of self-regulation and associated support system have attracted more attention in recent years, especially in developed countries. This review describes the mechanism and summarizes the potential factors that influenced self-regulation of driving amongst older adults to provide new insights into a broader framework for transportation and safe mobility. Methods : We systematically searched 12 online databases for qualitative studies exploring the experiences of older adults aged 60 years and above on their decision to self-regulate their driving. Thematic synthesis was performed to identify elements influencing driving reduction and cessation. The confidence profile of each findings from the meta-synthesis was appraised using the Confidence in the Evidence from Reviews of Qualitative research (CERQual) tool. Results : A total of 17 studies representing views of 712 older adults from four countries were included. Three major themes were identified with each representing a transition phase that can either facilitate or hinder older drivers from ceasing completely or reducing their driving, when transitioning from pre-decision phase to post-cessation phase. Conclusions : Our findings suggest that there is a mismatch between the current traffic collation prevention measures, such as age-specific mandatory license renewal system and travel needs of older adults. As such, it is time for the authorities, researchers, and public from various fields and perspectives to collaborate, sustain, and improve safety and mobility in older adults. Practical applications: Adequate regulations and guidelines from the medical community and legal authorities are warranted to assist older adults and caregivers. Social support (e.g., feedback, assurance, or transportation support) from family members, friends, and healthcare professionals are crucial for a smooth transition. Provision of alternative transportations in rural areas are needed and future interventions should focus on engaging and educating older adults to consider alternative transportation modes for mobility. Age-specific mandatory license renewal procedure can be useful in screening for at-risk groups. Highlights: Self-awareness, priority for driving, and availability of support system are important contributors to driving self-regulation. Educational programs, support and policy changes are needed to encourage self-regulation Regulations, alternative transportation, and age-specific license renewal system are needed in developing countries Limited research on older adults' transportation and safe mobility exists in developing countries